Leakage conduction mechanism of amorphous Lu2O3 high-k dielectric films fabricated by pulsed laser ablation - Yuan, C. L. (2013)
Amorphous Lu2O3 thin films have been deposited on p-type (111) Si substrates by pulsed laser deposition (PLD). A equivalent oxide thickness (EOT) of 1.16 nm with a leakage current density of 4×10−5 A/cm2 at 1 V accumulation bias was obtained for 4.5 nm thick Lu2O3 thin film deposited at room temperature followed by post-deposition anneal (PDA) at 600 °C in oxygen ambient. The leakage conduction mechanisms of amorphous Lu2O3 films were investigated. It was found that the Poole-Frenkel (P-F) emission is the dominant conduction mechanism at high electric field region.